The Impact of Smartphones on Students’ Psychology, Emotions, Physical Health, Management, Social Life, and Academic Performance - Marleny Leasa; Albertus Fenanlampir; Natcha Mahapoonyanont; Nathalie Elischeva Kailola; John Rafafy Batlolona (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to analyze the impact of smartphone usage on students’ psychological, emotional, physical, social, and academic aspects at Pattimura University. A quantitative approach was employed using a voluntary survey method involving 546 students aged 18–24 years. Data were collected through a Likert-scale questionnaire and analyzed using percentage techniques. The findings indicate that excessive smartphone use has a significant multidimensional impact on students. Approximately 57.96% of respondents reported intensive social media usage patterns that interfere with concentration, while 65.69% showed notable psychological and emotional effects, including anxiety and mood disturbances. Regarding physical health, respondents reported sleep disturbances, eye strain, and reduced physical activity. Some also acknowledged that smartphone use affects social relationships and productivity, including increased procrastination and decreased academic focus. Despite these negative impacts, students demonstrated awareness of the importance of managing smartphone usage through strategies such as time limitation and digital detox. It can be concluded that uncontrolled smartphone use contributes to decreased academic performance and well-being, although adaptive skills and self-regulation may mitigate these effects.